INTEGRATION OF TECHNOLOGY IN THE PRE-SERVICE TEACHERS FOR EDUCATIONAL MANAGEMENT; THROUGH CURRICULUM IN GHANA - Gorni, Richard Lionel; Saud, Udin Syaefudin; Sumarto, Sumarto; Nurdin, Diding (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to investigate the integration of technology in the preparation of prospective teachers for educational management through the curriculum in Ghana. Utilizing a qualitative approach, the study analyzes how technology is embedded in learning and how prospective teachers respond to it in the context of education management. The main focus of this research is on the concept and use of technology in the educational process to enhance the understanding and skills of prospective teachers.  However, the study found that the curriculum policies, structure, and guidelines for pre-service teachers lack a clear vision for effectively integrating technology. Interviews with policymakers indicated their recognition of the importance of technology integration but also revealed the lack of investment hindered its progress. Drawing on the study's findings and existing research, context-specific recommendations are proposed, focusing on promoting innovative technology-based pedagogical models and developing effective leadership. The study involved participants from a teacher preparation program in Ghana, with data collection conducted through in-depth interviews, classroom observations, and curriculum document analysis. Data were analyzed using an inductive approach to identify common patterns in technology integration and prospective teachers' responses to it. The results of this study are expected to provide insights into the extent to which technology is integrated in the teacher preparation curriculum in Ghana, as well as its impact on teacher candidates' readiness to manage education. The practical implications of this study can provide recommendations for improving the teacher education curriculum, adapting teaching strategies to technological developments, and increasing the effectiveness of teacher preparation in the digital era. The findings can provide valuable guidance for policy makers, educational institutions and educators to ensure that prospective teachers have the relevant and necessary skills to face future educational demands.